Acute and chronic toxicity of aluminum to a unionid mussel (Lampsilis siliquoidea) and an amphipod (Hyalella azteca) in water‐only exposures. (28th December 2017) - Wang, Ning; Ivey, Chris D.; Brunson, Eric L.; Cleveland, Danielle; Ingersoll, Chris G.; Stubblefield, William A.; Cardwell, Allison S.
Abstract: The US Environmental Protection Agency (USEPA) is reviewing the protectiveness of the national ambient water quality criteria (WQC) for aluminum (Al) and compiling a toxicity data set to update the WQC. Freshwater mussels are one of the most imperiled groups of animals in the world, but little is known about their sensitivity to Al. The objective of the present study was to evaluate acute 96‐h and chronic 28‐d toxicity of Al to a unionid mussel ( Lampsilis siliquoidea ) and a commonly tested amphipod ( Hyalella azteca ) at a pH of 6 and water hardness of 100 mg/L as CaCO3 . The acute 50% effect concentration (EC50) for survival of both species was >6200 μg total Al/L. The EC50 was greater than all acute values in the USEPA acute Al data set for freshwater species at a pH range of 5.0 to <6.5 and hardness normalized to 100 mg/L, indicating that the mussel and amphipod were insensitive to Al in acute exposures. The chronic 20% effect concentration (EC20) based on dry weight was 163 μg total Al/L for the mussel and 409 μg total Al/L for the amphipod. Addition of the EC20s to the USEPA chronic Al data set for pH 5.0 to <6.5 would rank the mussel ( L. siliquoidea ) as the fourth most sensitive species and the amphipod ( H. azteca ) as the fifth most sensitive species, indicating the 2 species were sensitive to Al in chronic exposures. The USEPA‐proposed acute and chronic WQC for Al would adequately protect the mussel and amphipod tested; however, inclusion of the chronic data from the present study and recalculation of the chronic criterion would likely lower the proposed chronic criterion. Environ Toxicol Chem 2018;37:61–69. Published 2017 Wiley Periodicals Inc. on behalf of SETAC. This article is a US government work and, as such, is in the public domain in the United States of America.